RUANG BANACH PADA RUANG BARISAN l1, lp DAN l~ - Alwi, Wahidah (Teknosains, 2014)
The main object of the vectors are the vectors can be added together and generate a vector, and produces a number is multiplied by another vector. Any set of objects with properties like this are called "vector space". Mathematical structure to be defined is a Banach space. Clearly defined Banach space vector space of real / complex normed and complete (with respect to the norm)